Конспект роду Melilotus (Fabaceae) флори України - Крицька, Л.І. (Український ботанічний журнал, 2014)
В статье приводятся данные, полученные в результате
критической обработки рода Melilotus Mill. флоры Украины.
Усовершенствована система рода, включающая два подрода,
четыре секции, три подсекции, четыре ряда. Описаны две
новые секции, три подсекции, три ряда. Для каждого вида
указаны синонимика и номенклатурный тип. Составлен
ключ для определения видов Melilotus. Приведены сведения
об экологической приуроченности и географическом
распространении видов. The article provides critically reviewed data on the
genus Melilotus Mill. in the flora of Ukraine. The system of the
genus, which includes 2 subgenera, 4 sections, 3 subsections, and
4 series, was amended. Two new sections, 3 subsections, and 4 new
series have been described. The synonymy and nomenclatural
types are given for each species. A new key to Melilotus Mill.
Species Occurring in Ukraine is proposed. Information about
ecological conditions and geographical distribution of these
species is provided as well.